2017
DOI: 10.1111/aji.12760
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular signal‐regulated kinase 1/2 triggers angiogenesis in human ectopic endometrial implants by inducing angioblast differentiation and proliferation

Abstract: Enhanced ERK1/2 activity in angioblasts by such peritoneal factors as VEGF, E induces proliferation to trigger ectopic endometrial angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…It can be explained that which signals or signaling pathways leads the endometrial cells to migrate, implant, grow, invade, and create a microenvironment. Since the MAPK signaling pathway crosstalk with the immune system elements and play role in angiogenesis, it is also possible to gain insight into the microenvironment that they create for their survival at the site of involvement 42, 64, 65 . Studies on the link between endometriosis and MAPK signaling pathway will provide more insight into the underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It can be explained that which signals or signaling pathways leads the endometrial cells to migrate, implant, grow, invade, and create a microenvironment. Since the MAPK signaling pathway crosstalk with the immune system elements and play role in angiogenesis, it is also possible to gain insight into the microenvironment that they create for their survival at the site of involvement 42, 64, 65 . Studies on the link between endometriosis and MAPK signaling pathway will provide more insight into the underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…65 This study which is very important for interpretation of the pro-angiogenic microenvironment in endometriosis showed that ERK signaling pathway activation is one of the triggers of human ectopic endometrial angiogenesis which might lead the severity of disease. 65 The correlation between Bcl-2, CD147 and ERK signaling pathway in human endometriosis was showed and reported that the activation of ERK signaling pathway in endometriotic lesions leads to the Bcl-2 activation which is a suppressor of intrinsic apoptosis pathway. The role of the ERK signaling pathway in reduced apoptosis and so enhanced cell survival in human endometriosis was showed.…”
Section: Erk Mapk Signaling Pathwaymentioning
confidence: 94%
See 2 more Smart Citations
“…The mobility, EMT and proliferation of human It is reported that the level of phosphorylated ERK was significantly higher in endometriotic lesions than in endometrial tissues. 31,32 And the activated ERK regulated over 160 proteins, which involved with the cell proliferation, apoptosis, angiogenesis and migration in endometriosis. [33][34][35] As exhibited in previous results, oes- transcriptional activities in cells.…”
Section: Discussionmentioning
confidence: 99%